Development of metarhizium anisopliae as a mycoinsecticide: from isolation to field performance - Tupe, Santosh G.; Pathan, Ejaj K.; Deshpande, Mukund V. (Jove-Journal of Visualized Experiments, 2017)
A major concern when developing commercial mycoinsecticides is the kill speed compared to that of chemical insecticides. Therefore, isolation and screening for the selection of a fast-acting, highly virulent entomopathogenic fungus are important steps. Entomopathogenic fungi, such as Metarhizium, Beauveria, and Nomurea, which act by contact, are better suited than Bacillus thuringiensis or nucleopolyhedrosis virus (NPV), which must be ingested by the insect pest. In the present work, we isolated 68 Metarhizium strains from infected insects using a soil dilution and bait method. The isolates were identified by the amplification and sequencing of the ITS1-5.8S-ITS2 and 26S rDNA region. The most virulent strain of Metarhizium anisopliae was selected based on the median lethal concentration (LC50) and time (LT50) obtained in insect bioassays against III-instar larvae of Helicoverpa armigera. The mass production of spores by the selected strain was carried out with solid-state fermentation (SSF) using rice as a substrate for 14 days. Spores were extracted from the sporulated biomass using 0.1% tween-80, and different formulations of the spores were prepared. Field trials of the formulations for the control of an H. armigera infestation in pigeon peas were carried out by randomized block design. The infestation control levels obtained with oil and aqueous formulations (78.0% and 70.9%, respectively) were better than the 63.4% obtained with chemical pesticide.

Optimization for the production of mycelial biomass from Benjaminiella poitrasii to isolate highly deacetylated chitosan - Mane, S. R.; Pathan, Ejaj K.; Kale, D.; Ghormade, Vandana; Gadre, Ramchandra V.; Rajamohanan, Pattuparambil Ramanpillai; Badiger, Manohar V.; Deshpande, Mukund V. (Journal of Polymer Materials, 2017)
Benjaminiella poitrasii, a dimorphic zygomycetous fungus contains more chitosan in the mycelial cell wall than the cell wall of its yeast form. The optimized medium containing yeast extract, peptone, MgSO4, KH2PO4, trace metals (Fe2+, Mn2+ Zn2+ and Co2+ ) solution and 1% starch produced 10-12 g/L(dry wt.) of mycelial biomass in 48 h in a 2L fermenter. Using 1N NaOH treatment from 1 g of dried biomass 51.00 ± 0.52 mg of chitosan of 42.82 KDa molecular weight and 94.24 % degree of deacetylation was extracted. With Metarhizium anisopliae chitin deacetylase (CDA), chitosan yield was 59.00 ± 0.84 mg while treatment with CDA of B. poitrasii it was 78.05 ± 0.58 mg/g of dry wt. of biomass. The chitosan dissolved in 2% acetic acid showed higher antifungal activity against Candida albicans (MIC90 0.025 mg/mL) and Candida glabrata (MIC90 0.2 mg/mL) than chitosan extracted from marine source (MIC90 >1.6 mg/mL) suggesting use of fungal chitosan in healthcare.

Selection of reference genes for quantitative real-time RT-PCR assays in different morphological forms of dimorphic zygomycetous fungus Benjaminiella poitrasii - Pathan, Ejaj K.; Ghormade, Vandana; Deshpande, Mukund V. (Plos One, 2017)
Benjaminiella poitrasii, a dimorphic non-pathogenic zygomycetous fungus, exhibits a morphological yeast (Y) to hypha (H) reversible transition in the vegetative phase, sporangiospores (S) in the asexual phase and zygospores (Z) in the sexual phase. To study the gene expression across these diverse morphological forms, suitable reference genes are required. In the present study, 13 genes viz. ACT, 18S rRNA, eEF1a, eEF-Tu, eIF-1A, Tuba, Tub-b, Ubc, GAPDH, Try, WS-21, NADGDH and NADPGDH were evaluated for their potential as a reference, particularly for studying gene expression during the Y-H reversible transition and also for other asexual and sexual life stages of B. poitrasii. Analysis of RT-qPCR data using geNorm, normFinder and BestKeeper software revealed that genes such as Ubc, 18S rRNA and WS-21 were expressed at constant levels in each given subset of RNA samples from all the morphological phases of B. poitrasii. Therefore, these reference genes can be used to elucidate the role of morpho-genes in B. poitrasii. Further, use of the two most stably expressed genes (Ubc and WS-21) to normalize the expression of the ornithine decarboxylase gene (Bpodc) in different morphological forms of B. poitrasii, generated more reliable results, indicating that our selection of reference genes was appropriate.

Biochemical and molecular aspects of dimorphism in fungi - Pathan, Ejaj K.; Ghormade, Vandana; Panmei, Redeemson; Deshpande, Mukund V. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
Most of the eukaryotic differentiation processes are unidirectional. However, fungi have the ability to grow reversibly as unicellular yeast (Y) or as filamentous hypha (H) in response to the specific strain-dependent environmental stimuli. Such a phenomenon known as “dimorphism” is not limited to a specific class of fungi. Most of the plant, human, and insect pathogenic fungi show Y-H and reversible morphogenesis, associated with their saprophytic to pathogenic change, for survival and proliferation in the host. In this chapter, we have described the factors stimulating dimorphism, the signal transduction pathways induced by these stimuli, changes in the gene/protein expression patterns due to a cascade of these signals, and, finally, translation of this genotypic effect into phenotypic change, i.e., the morphological outcome. The process of fungal differentiation and formation of tumor cells follow the same regulatory series of events, involving cAMP, MAP, and RAS kinase cascades. Therefore, the molecules inhibiting Y-H transition in fungi can be explored for their anticancer potential.

Molecular studies of NAD- and NADP-glutamate dehydrogenases decipher the conundrum of yeast-hypha dimorphism in zygomycete Benjaminiella poitrasii - Pathan, Ejaj K.; Ghormade, Vandana; Panwar, Sneh Lata; Prasad, Rajendra; Deshpande, Mukund V. (Fems Yeast Research, 2019)
Benjaminiella poitrasii, a zygomycete, shows glucose- and temperature-dependent yeast (Y)-hypha (H) dimorphic transition. Earlier, we reported the biochemical correlation of relative proportion of NAD- and NADP-glutamate dehydrogenases (GDHs) with Y-H transition. Further, we observed the presence of one NAD-GDH and two form-specific NADP-GDH isoenzymes in B. poitrasii. However, molecular studies are necessary to elucidate the explicit role of GDHs in regulating Y-H reversible transition. Here, we report the isolation and characterization of one NAD (BpNADGDH, 2.643 kb) and two separate genes, BpNADPGDH I (Y-form specific, 1.365 kb) and BpNADPGDH II (H-form specific, 1.368 kb) coding for NADP-GDH isoenzymes in B. poitrasii. The transcriptional profiling during Y-H transition showed higher BpNADPGDH I expression in Y cells while expression of BpNADPGDH II was higher in H cells. Moreover, the yeast-form monomorphic mutant (Y-5) did not show BpNADPGDH II expression under normal dimorphism triggering conditions. Transformation with H-form specific BpNADPGDH II induced the germ tube formation in Y-5, which confirmed the cause-effect relationship between BpNADPGDH genes and morphological outcome in B. poitrasii. Interestingly, expression of H-form specific BpNADPGDH II also induced germ tube formation in human pathogenic, non-dimorphic yeast Candida glabrata, which further corroborated our findings.
Keywords: Benjaminiella poitrasii; Candida glabrata; differential gene expression; dimorphism; monomorphic mutant; NAD/NADP-glutamate dehydrogenase; yeast-hypha transition

Puzzle of highly virulent Metarhizium anisopliae strains from Annona squamosa fields against Helicoverpa armigera - Pathan, Ejaj K.; Deshpande, Mukund V. (Journal of Basic Microbiology, 2019)
In our search for indigenous virulent strains of the entomopathogenic fungi, we observed that Metarhizium isolates from soils associated with Annona squamosa (custard apple) have higher virulence (>90% mortality of Helicoverpa armigera larvae at 1/10(th) spore concentration) than strains isolated from Solanum lycopersicum (tomato) fields. Proteomic analysis revealed two insecticidal cyclopeptides of A. squamosa origin in the M. anisopliae strains that led to higher virulence against H. armigera. Transcriptomic and genomic data indicated that M. anisopliae strains and A. squamosa had more than 20 genes in common, including those for cyclic hexapeptide synthase, non-ribosomal peptide synthetase, and plant cyclotide genes, which are involved in the biosynthesis of insecticidal cyclopeptides. These genes were absent in M. anisopliae strains isolated from the S. lycopersicum fields. Further, these strains can establish an endophytic relationship with A. squamosa suggesting that these rhizospheric strains originally could be endophytes, which were eventually released into the soil. Further, Metarhizium strains associated with Capsicum annuum (chili), Azadirachta indica (neem), and Carica papaya (papaya) - plants with insecticidal properties - also had higher virulence against H. armigera. Thus exploration of rhizospheres of plants producing insecticidal metabolites to isolate entomopathogenic fungi, per se, could be a viable strategy in agricultural for crop protection.
Keywords: Annona squamosa; Biocontrol; endophyte; entomopathogen; Helicoverpa armigera; horizontal gene transfer; insecticidal peptides; Metarhizium; natural transformation

NADP-dependent glutamate dehydrogenases in a dimorphic zygomycete Benjaminiella poitrasii: purification, characterization and their evaluation as an antifungal drug target - Pathan, Ejaj K.; Kulkarni, Anand M.; Prasanna, Nallaballe V. L.; Ramana, V, Chepuri; Deshpande, V, Mukund (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: It has been reported that the genes coding for NADP-dependent glutamate dehydrogenases (NADP-GDHs) showed a cause-effect relationship with Yeast-Hypha (Y-H) reversible transition in a zygomycete Benjaminiella poitrasii. As Y-H transition is significant in human pathogenic fungi for their survival and proliferation in the host, the NADP-GDHs can be explored as antifungal drug targets. Methods: The yeast-form specific BpNADPGDH I and hyphal-form specific BpNADPGDH II of B. poitrasii were purified by heterologous expression in E. coll. BL-21 cells and characterized. The structural analogs of L-glutamate, dimethyl esters of isophthalic acid (DMIP) and its derivatives were designed, synthesized and screened for inhibition of NADP-GDH activity as well as Y-H transition in B. poitrasii, and also in human pathogenic Candida albicans strains. Results: The BpNADPGDH I and BpNADPGDH II were found to be homo-hexameric proteins with native molecular mass of 282 kDa and 298 kDa, respectively and subunit molecular weights of 47 kDa and 49 kDa, respectively. Besides the distinct kinetic properties, BpNADPGDH I and BpNADPGDH II were found to be regulated by cAMP-dependent- and Calmodulin (CaM) dependent- protein kinases, respectively. The DMIP compounds showed a more pronounced effect on H-form specific BpNADPGDH II and inhibited Y-H transition as well as growth in B. poitrasii and C. albicans strains. Conclusion: The present study will be useful to design and develop antifungal drugs against dimorphic human pathogens using glutamate dehydrogenase as a target. Significance: Glutamate dehydrogenases can be explored as a target against human pathogenic fungi.
Keywords: Antifungal compound; Benjaminiella poitrasii; Candida albicans; Dimethyl esters and amides of isophthalic acid; dimorphism; Enzyme inhibition; NADP-glutamate dehydrogenases

New record of larval-pupal endoparasitoid Exorista deligata parasitising Indian Tea looper Hyposidra talaca from India - Sharma, Pooja V.; Das, Tamal; Mukherjee, Susmita; Pathan, Ejaj K.; Rahman, Azizur; Gathalkar, Ganesh B. (Phytoparasitica, 2024)
This is the first record of Exorista deligata (Pandell & eacute;, 1896) (Diptera: Tachinidae) as a parasitoid of Hyposidra talaca (Walker, 1860) (Lepidoptera: Geometridae) from India. H. talaca is a major and new emerging defoliator of the Tea plant Camellia sinensis (L) Kuntze (Theaceae). It completes multiple generations per year without diapause on C. sinensis, resulting in heavy crop loss. The field-collected larvae/pupa of H. talaca were checked for parasitoid infestations and reared until either the host or parasitoid emerged. The parasitoid was identified as E. deligata with morphological characteristics and confirmed by the mitochondrial cytochrome oxidase subunit-I (COX-CO1) gene sequencing technique. The parasitoid is infrequent with unexplored parasitic biology. It parasitises the larva and completes its lifecycle inside the developing H. talaca by entirely devouring the host. The mean percent parasitisation caused by E. deligata studied herein was 25.4% (range 5.88%-57.69%). Based on its parasitisation ability, we suggest the species could be a potential biological control agent to address the damage mitigation caused by the tea looper pest, H. talaca.
Keywords: Biocontrol; Exorista deligata; Hyposidra talaca; Invasive pest; Parasitisation

Endophytic entomopathogenic fungi: the next frontier in mycological biocontrol - Patil, Karan S.; Gathalkar, Ganesh B.; Pathan, Ejaj K. (World Journal of Microbiology & Biotechnology, 2026)
Entomopathogenic fungi (EPF) are eco-friendly alternatives to chemical pesticides. However, high costs, the instability of the formulations, sensitivity to environmental factors and variability in virulence limit adoption by farmers. We argue that these problems can be overcome by using EPF strains established as endophytes. The ability of endophytic entomopathogenic fungi (EEPF) to modulate the release of volatiles to attract the predators of insect pests positions them as dual-purpose biocontrol agents in agriculture. As endophytes, these fungi are persistent, lowering the costs for pest control. Endophytic entomopathogenic fungi can also promote plant growth and improve tolerance to abiotic stress. Research on the molecular mechanisms underlying plant tissue colonization by EEPF, their persistence in plants and virulence towards insects suggests that EEPF acquire virulence factors and metabolic versatility through horizontal gene transfer from plants. Therefore, establishing and maintaining EPF as endophytes within plants may compensate for the loss of virulence associated with repeated in vitro subculturing of EPF on artificial media. However, despite these potential advantages of EEPF, challenges still remain, such as variability in endophytic colonization under field conditions, host specificity, ecological risks, and scalability. This review critically evaluates these limitations, focusing on well-studied genera, such as Metarhizium, Beauveria, and Lecanicillium, and outlines future directions for improving the reliability of the application of EEPF. By integrating ecological, molecular, and applied perspectives, we provide a comprehensive and updated framework that positions EEPF as next-generation biocontrol agents in sustainable agriculture.Graphical AbstractEndophytic entomopathogenic fungi protect plants by infecting insect pests and emitting volatiles to attract the natural predators of insect pests. They also promote plant growth by improving the nitrogen fixation and nutrient cycling
Keywords: ; Beauveria; Metarhizium; Biological control; Endophytic fungi; Entomopathogens; horizontal gene transfer; Plant-fungus interactions; Sustainable agriculture